From visitors to vitality: How relational populations support regional revitalization in aging urban and rural areas - Han-Jen Niu; En-Tzu Wu; Chen-Yun Yen; Mei-Jen Chen; Chun-Chieh Yu (Sustainable Futures)
Urban shrinkage, exacerbated by population aging, is a critical global issue, with particularly severe effects in Asia. This study introduces the concept of the ''relational population,'' highlighting the potential of tourists as long-term contributors to regional revitalization. Unlike traditional tourist roles, this research explores how tourists can foster regional vitality by becoming emotionally invested stakeholders. Focusing on Tamsui, a shrinking urban and rural area, this study aims to transform tourists into a relational population, deepening their connection to Tamsui's cultural heritage. Using structural equation modeling to analyze data from 473 survey responses, the findings underscore the significant influence of place attachment on tourist engagement, emotional cohesion, and co-creation of value. The results suggest a paradigm shift: tourists are evolving from mere economic agents to essential participants in regional revitalization, particularly in addressing demographic challenges.